Organization and digitization of information about buildings and civil engineering works, including building information modelling (BIM) - Information management using building information modelling : - International Organization for Standardization
This document specifies requirements for information management, in the form of a management process, within the context of the delivery phase of assets and the exchanges of information within it, using building information modelling. This document can be applied to all types of assets and by all types and sizes of organizations, regardless of the chosen procurement strategy.